Perbedaan Pertumbuhan Tanaman Yang Diletakkan Di Tempat Terang Dengan Tempat Gelap - Hulu, Stefani Angel Kristin; Harefa, Wendi Warisman; Waruwu, Basri Kalvianus; Frans Zefrindo Two Waruwu; Erwin Saputra Gea; Ariel Nezer Perlindungan Halawa (CV. SINAR HOWUHOWU, 2025)
This study aims to explore the effect of lighting on plant growth and development. Two different lighting conditions, namely bright and dark places, were selected as independent variables in this study. The samples used in this study were mung bean and corn (Phaseolus vulgaris) plants. The selection of mung bean and corn plants as samples was based on several considerations, including: Mung bean and corn plants are easy to plant and care for, so they are suitable for research that requires intensive observation over a certain period of time. The results of the study showed that plants placed in bright places showed better growth compared to plants placed in dark places. Plants in bright places had higher plant heights, more leaves, and greater leaf weight. This shows that sufficient lighting is an important factor in supporting plant gowth. The conclusion of this study is that lighting plays an important role in plant growth. Adequate lighting can increase photosynthesis, which in turn supports plant growth and development. This study provides insight into the importance of lighting in agriculture and can be a basis for further research on optimizing lighting conditions for optimal plant growth.